2017
DOI: 10.1016/j.neucom.2016.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Robust adaptive neural control for a class of non-affine nonlinear systems

Abstract: This paper addresses the adaptive neural tracking control problem for a class of uncertain non-affine nonlinear system with non-affine function being semi-bounded and possibly non-differentiable. Compared with traditional control schemes, the proposed scheme can be applied to a more general class of non-affine nonlinear system, and relaxes constraint conditions as follows: firstly, the assumption that non-affine function must be differentiable is canceled, and only a continuous condition for non-affine functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The approximation curves of x 1 and x 2 are shown in Fig. 2, which implies the effectiveness of approximation method (7). Figs 3 and 4 demonstrate the good tracking performance of system states and r confronted with unknown compound disturbance, actuator faults.…”
Section: Simulation Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…The approximation curves of x 1 and x 2 are shown in Fig. 2, which implies the effectiveness of approximation method (7). Figs 3 and 4 demonstrate the good tracking performance of system states and r confronted with unknown compound disturbance, actuator faults.…”
Section: Simulation Resultsmentioning
confidence: 72%
“…14, the estimation disturbance changes obviously at t = 15s and then approximates compound disturbance in finite time. From the simulation results (Figs 1-14), it is concluded that non-affiine UAV helicopter with unknown compound disturbance and actuator faults can track not only constant desired signal but also time-varying desired signal in finite time based on the approximation method (7), ATSMDO (8) and controller (30), (40) and (47)). In Figs 5 and 13, it is obvious that actuator faults occurs at t = 15 and last later.…”
Section: Simulation Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent years have witnessed a great amount of research in approximation-based adaptive control for nonlinear uncertain systems due to both the practical need and theoretical challenges [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In these works, neural networks (NNs) or fuzzy-logic systems (FLS) are typically used to approximate nonlinear functions with little knowledge of system to be controlled, which has effectively removed the restrictive matching conditions for system uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…There exist many practical systems which are non-affine in the control input. For example: the model of aircraft dynamics (Boškovic, Chen, & Mehra, 2004), underwater vehicles (Geranmehr & Nekoo, 2015), active magnetic bearings (Tombul, Banks, & Akturk, 2009); electromagnetic levitation (Gutierrez & Ro, 2005) and etc (Ríos, Punta, & Fridman, 2017;Shi, Dong, Xue, Chen, & Zhi, 2017;Song & Song, 2014). Because of the complex structure of non-affine systems, the Lyapunov-based controllers have not been fully studied for these systems and most of the designed controllers for the non-affine systems are based on the non-model based methods like fuzzy or neural network controllers (Chien, Wang, Leu, & Lee, 2011Gao, 2017;Labiod & Guerra, 2010).…”
Section: Introductionmentioning
confidence: 99%